Assessing the cost of onshore wind development scenarios: Modelling of spatial and temporal distribution of wind power for the case of Poland. (July 2019) - Sliz-Szkliniarz, B.; Eberbach, J.; Hoffmann, B.; Fortin, M.
Abstract: Wind energy plays a key role in the transition to a low-carbon European energy system. The implementation of European and national targets for wind energy expansion is, however, challenged by technical, environmental, economic and social acceptance aspects. Further research on wind power expansion is compelled due to dynamic aspects such as land-use fluctuations, evolution of wind turbine technology, associated cost, and other factors. For that reason, a systematic approach for exploring future scenarios of onshore wind power development under techno-economic aspects and quantitative aspects of social acceptance (distributive justice and regulatory framework) was developed. The model was developed in Python, PostgreSQL and SQliteDB and encompasses a high-resolution GIS-based assessment of potential locations for wind turbines. Homogenous input data allows for analysing the wind power potential across Europe. Poland was chosen as a case study to examine the impact of the distance regulation introduced in 2016 and its subsequent amendments, which are relevant for onshore wind power development foreseen in the EU reference scenario 2016 for 2030. The findings show that Poland can reach the target of 10.3 GW set by the EU scenario at Levelized Cost of Electricity below €60/MWh. The transparent modelling framework and findings can support the decision making process on wind energy expansion, which is in the hands of policy makers, private investors and local citizens. Highlights: Transferable approach for the assessment of wind power potentials across Europe. Distance regulation and spatial distribution to affect onshore wind energy costs. Method integrating quantifiable aspects of social acceptance. Case study for Poland and its onshore wind capacity target to be reached by 2030.